2019
DOI: 10.1109/msp.2019.2909074
|View full text |Cite
|
Sign up to set email alerts
|

Radar-on-Chip/in-Package in Autonomous Driving Vehicles and Intelligent Transport Systems: Opportunities and Challenges

Abstract: This survey paper addresses the signal processing challenges for the design of radar-on-chip/in-package in the autonomous driving era, taking into account recent integration trends and technology capabilities. Radar signal processing platform specifications are discussed, and the radar sensor is compared to other competing sensors, such as Lidars and ultrasonics and video cameras, that aim at detecting still or moving objects too, and at measuring their motion parameters. This survey paper first focuses on sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Autonomous driving is a safety critical application, as specified also in functional safety standards like ISO26262, with strict requirements in terms of real-time (both throughput and latency) [1,2]. In Levels 1 and 2 of the SAE autonomous driving scale [1] just an assistance to human driver is needed. Hence, signal processing based on deterministic algorithms is still enough, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autonomous driving is a safety critical application, as specified also in functional safety standards like ISO26262, with strict requirements in terms of real-time (both throughput and latency) [1,2]. In Levels 1 and 2 of the SAE autonomous driving scale [1] just an assistance to human driver is needed. Hence, signal processing based on deterministic algorithms is still enough, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, signal processing based on deterministic algorithms is still enough, e.g. FFT-based processing of Frequency Modulated Continuous Wave Radar (FMCW) as done in [1]. Instead, for high autonomous driving levels, from L3 to L5, the complexity of the scenario and the needs of signal processing are very high, not only for sensing, but also for localization, navigation, decision and actuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where Y ∈ C M N ×Q contains the received data after matched filtering, Z is the spatially and temporally white additive noise, C T ∈ C P ×Q contains the reflection coefficients of P targets corresponding to Q pulses, and A ∈ C M ×P and B ∈ C N ×P denote the respective steering matrices for transmit and receive arrays. Arranging the matched-filter outputs as a tensor Y ∈ C M ×N ×Q and following the definitions of the matrix unfoldings in Section II-B2, it can be observed that model (52) represents the PARAFAC decomposition. As such, target parameter estimation can proceed within the PARAFAC framework.…”
Section: A Tensor Techniques For Target Parameter Estimation In Mimo Radarmentioning
confidence: 99%
“…Any sensor that goes on the hard hat must be small, lightweight, and robust to rugged environments like construction or mining. Recent advances in microelectronics and signal processing have provided us with minimal, low cost and high-performance Doppler radars [56][57][58]. Our idea is to mount CW radars on hard hats and to sense the surroundings.…”
Section: Smart Hard Hatsmentioning
confidence: 99%